(untitled) (Journal of Scientific Research, 2014)
Magnetite nanoparticles have been prepared by using sol-gel auto combustion technique. The samples are prepared by using different concentrations of fuel. Structural characterization has been done using X-Ray diffraction technique and it was observed that fuel concentration can affect the structural properties of Magnetite nanoparticles. The dielectric properties for all the samples such as dielectric constant (??), dielectric tangent loss (tan ?) and dielectric loss factor (??) have been studied as a function of frequency and temperature in the range 10 Hz20 MHz and it was found that these nanoparticles can be used in microwave devices because of their good dielectric behavior. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.17938 J. Sci. Res. 6 (3), 399-406 (2014)